Worldviews, Issue Knowledge, and the Pollution of a Local Science Information Environment. (April 2016) - Ahern, Lee; Connolly-Ahern, Colleen; Hoewe, Jennifer
Research in motivated reasoning supports the notion that sociopolitical identity moderates the impact of knowledge on attitudes toward science issues. However, science knowledge and sociopolitical orientation have been measured in different ways, and the results have not been entirely consistent. In this study, 964 adults participated in an online survey-experiment examining their reactions to a message about local water quality. Results show that while issue-specific knowledge predicts increased environmental science public policy support, "polluting" the information environment with already politicized message frames activates sociopolitical orientation as a moderator and, among certain groups, reverses the direction of the relationship.